Pendampingan Business Trust Pada Womenpreneur Melalui Pemanfaatan Modal Sosial dan Personal Branding di Kelurahan Wonocolo Taman Sidoarjo - Ragil Cahya Satria; Muhammad Rif'al Rafi; Muhammad Arifin; Achmad Zainuddin; Dodik Wahyono (LPPM Universitas Yudharta Pasuruan, 2021)
Assistance to womenpreneurs in utilizing social capital and personal branding in the Sidoarjo Park area is one of the efforts that can be made to care more about social issues, especially taking sides with women to develop their potential so that the strengthening of the family economy can be more advanced. This assistance also aims to make all levels of society able to rise from any calamity, including the pandemic. In addition, this assistance is expected to raise awareness about the importance of providing mutual support and paying attention to the potential of family members. Conditioning conducive mentally and spiritually is the first step before strengthening with research, so that the mindset as a mowenpreuner is formed from the start. The approach in this service uses the participatory action research (PAR) method. At the implementation stage of the service program, it is carried out using a community organizer (CO) approach, with a personal approach strategy, a community approach, and capacity building. The result of this assistance is an increase in women's belief in Taman Sidoarjo that every individual is capable of becoming an entrepreneur. In addition, beliefs are concrete, real and can be quantified. Measurably, that trust affects the speed and cost of doing business. Nothing is faster than trust because trust is a function of character that includes both integrity and competence. Forming trust with one person will form trust with many people.